2017
DOI: 10.25135/rnp.62.16.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant and Anticholinesterase Activities of the Essential oil of Origanum rotundifolium Boiss. from Turkey

Abstract: Abstract:The essential oil was obtained by hydrodistillation from the aerial parts of Origanum rotundifolium Boiss. Its chemical content and composition were analyzed by using a gas chromatography (GC-FID) and gas chromatography-mass spectrometry (GC-MS). Total phenolic content of the essential oil was determined as 132.39 µg gallic acid equivalent by Folin-Ciocalteu's method and the major component was identified as carvacrol (56.8 %) along with p-cymene (13.1 %), (Z)--ocimene (5.4 %), -caryophyllene (3.9 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Furthermore, according to recent findings, different physiological and behavioral modes of action of essential oils and their components have been reported. For example, inhibition of adenosine triphosphatases (ATPases), acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) [76,96], and distribution in the octopamine and gamma-aminobutyric acid receptors (GABArs) have been documented [112]. Given that octopamine receptors are invertebrates-specific, the use of essential oils in pest management, with this mode of action, can be considered to be safe bioagents for mammals [112].…”
Section: Mode Of Pesticidal Actionmentioning
confidence: 99%
“…Furthermore, according to recent findings, different physiological and behavioral modes of action of essential oils and their components have been reported. For example, inhibition of adenosine triphosphatases (ATPases), acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) [76,96], and distribution in the octopamine and gamma-aminobutyric acid receptors (GABArs) have been documented [112]. Given that octopamine receptors are invertebrates-specific, the use of essential oils in pest management, with this mode of action, can be considered to be safe bioagents for mammals [112].…”
Section: Mode Of Pesticidal Actionmentioning
confidence: 99%
“…Many studies have confirmed that natural food ingredients and their products have potent neuroprotective effects (Liao et al., ; Oboh et al., ; Zhang, Luab, & Jianga, ). Recently, an increasing number of researches have become interested in identifying neuroprotective factors from natural materials, expecting to find a lot of novel neuroprotective ingredients (Özbek et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Total phenolics in AEF and EEF were measured by Folin-Ciocalteu reagent [4][5][6] and calculated as μg of GA equivalents (GAE) per one mg of dried extract. Total flavonoids in AEF and EEF were estimated using the AlCl 3 [9]. They were calculated as μg of quercetin equivalents (QE) per one mg dried extract.…”
Section: Present Studymentioning
confidence: 99%